The impact of COVID-19 on the work-life balance of collegiate athletic trainers - Jones, N.; Rynkiewicz, K. M.; Singe, S. M. (International Journal of Athletic Therapy & Training, 2022)
Context: The COVID-19 pandemic has potential ramifications on work-life balance for those working in health care. Purpose: The purpose of this study was to better understand COVID-19 on work-life balance and quality of life among collegiate athletic trainers. Method: Data for this study were generated from 636 eligible respondents (33 ± 9 years) representing Division I, II, and III (n = 360, n = 104, and n = 172, respectively) settings. Results: Four main themes emerged from consensual qualitative data analysis: mental health impact, social responsibility, work-life boundaries, and 24/7 work demands. Conclusion: The results suggest that collegiate athletic trainers are struggling to find work-life balance and must find ways to implement self-care practices.